ANALISIS YURIDIS ATAS PERAN PEMERINTAH DAERAH TERHADAP PELAKSANAAN TANGGUNG JAWAB SOSIAL PERUSAHAAN - Ade Yuliany Siahaan; Suhaidi Suhaidi; Sunarmi Sunarmi; Jelly Leviza (Universitas Sumatera Utara, 2018)
ABSTRACT The research shows that North Sumatera have not yet a regional regulations of CSR but the Local Governments has begun to focus on completing the discussion of that. Even do not have yet the regional regulations of CSR, the Local Government is already have role in corporate social responsibility implementation such as by supervising, receiving reports and cooperating in arrangements CSR. The thing that underlies the participation of local governments in the implementation of CSR is the decentralization policy. It’s just the role of The Local Government sometimes not in accordance with applicable law in Indonesia because The Local Government is still seems not to understand the true meaning of CSR and act over the limit. For it is suggested that the government should make more strict regulations related to the issue of sanctions. And for it is suggested that Local Governments of North Sumatera better to understand more about the truly of CSR’s meaning and simply supervise and provide legal certainty so that all parties (stakeholders) can receive the benefits of corporate social responsibility emplementation. Keyword : Juridical Analysis, Corporate Social Responsibility, and The Local Governments.